Neurotoxicity caused by lead present in food and environment: A review - Elena-Iuliana Flocea; Cosmin Ghelbere (International Journal of Agricultural Science and Food Technology - Peertechz Publications, 2022)
A problem we are facing more and more often has caught our attention. Neurotoxicity is caused by lead contamination of the environment and food chain. The purpose of this review is to present the harmful effects of lead on human health. In the long term, lead accumulated in the body can cause cognitive, motor, and behavioral changes. According to recent studies, lead is a real danger for children because it affects the development of the nervous system even in small amounts. This review also focused on suggesting a powerful antioxidant, vitamin C in the diet. Studies have shown that it has a possible neuroprotective role, being kept in high concentrations in the brain.